Ferment in the intercultural field : axiology/value/praxis - Starosta, William J.; Chen, Guo-Ming (International and intercultural communication annual ;, 2003)
This title examines how the field of intercultural communication has encouraged new techniques in the area of research. The editors, along with a diverse group of distinguished contributors, recall the 1983 topical issue of 'The Journal of Communication' which reported a critical turn and a shift of paradigms in communication research.